(untitled) (Research, Society and Development, 2021)
The use of traditional and/or emerging technologies are fundamental for adding value to fish, as well as the use of natural products that promote more than one benefit to the elaborated products. This study evaluated the use of natural pigments with antioxidant effect in the smoking of tilapia fillets, characterizing the yield, proximate composition, colorimetry, lipid oxidation and sensory profile. Tilapia fillets were immersed in brine (20% + 0.5% rosemary extract) containing 1.5% açaí, saffron and beet powder, in addition to a control treatment, without dye, for 20 minutes. The fillets were drained, dehydrated and subjected to a smoking process for 90 minutes. They were weighed every 30 minutes to assess the losses caused by the process. Losses ranged from 24.13 to 32.86% during the process. It was observed a lower moisture in the fillets of the control treatment. The inclusion of açaí and beetroot dyes provided a higher lipid content in the smoked fillets, while açaí provided a lower ash content. The fillets using beetroot and saffron showed greater color intensity and greater preference by evaluators in the sensory analysis. The analysis of thiobarbituric acid reactive substances indicated stability of the lipid portion for all treatments up to 30 days of storage. Therefore, the use of natural pigments with antioxidant action, in addition to promoting better product acceptance through improved appearance, also ensures oxidative stability for longer storage time, demonstrating a way of adding value to the fish.